The Priority of Building Ecological Transport System in Metropolises: Obstacles, Methods and Opportunities - Nawras Suliman (Вестник Российского экономического университета имени Г. В. Плеханова)
The article shows efficient ways of cutting the negative impact of transportation on the environment in metropolises as tools of passing-over to sustainable transportation system. The author identifies key ecological problems in metropolises – consequences of using transport, in particular, CO2 transport emissions are studied in view of their volumes and changes that took place during the last 5 years. It was revealed that all over the world transport damages the environment much more seriously than other industries. The author analyzed advanced methods of passing over from traditional to sustainable transport in different aspects (technical, infrastructural and cultural) in order to protect the environment in metropolises with due regard to economic interests. A lot of obstacles were found, such as time, mode of modern life in metropolises, inter-sectoral nature of transport, etc., which hinder the process of shaping sustainable transport systems in metropolises. As a result of the research the author confirms the necessity to work out a sustainable transport system, in spite of complexity of the process. Apart from that, three variants of shaping sustainable transport system were put forward: basic, standard and advanced.